2012
DOI: 10.1055/s-0031-1290656
|View full text |Cite
|
Sign up to set email alerts
|

A Transition-Metal-Free Cross-Coupling Reaction of Allylic Bromides with Aryl- and Vinylboronic Acids

Abstract: A cross-coupling reaction between aryl-and vinylboronic acids and various allylic bromides proceeded without the use of a transition-metal catalyst to give the corresponding allylated products in moderate to good yields. The use of an inorganic base (KF or Cs 2 CO 3 ) and a small amount of water is crucial in obtaining good performance in the present transition-metal-free reaction.The palladium-catalyzed cross-coupling reaction of allylic halides, 1 esters, 2 and alcohols 3 with organoboronic acids provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…32 The change of CH 2 Cl 2 for CHBr 3 together with an increase in the reaction temperature to 90ºC has permitted the reaction of electron-rich arylboronic acids with arylpropargylic bromides (13-84% yields). 32…”
Section: Transition-metal-free Suzuki Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The change of CH 2 Cl 2 for CHBr 3 together with an increase in the reaction temperature to 90ºC has permitted the reaction of electron-rich arylboronic acids with arylpropargylic bromides (13-84% yields). 32…”
Section: Transition-metal-free Suzuki Reactionsmentioning
confidence: 99%
“…Using Cs 2 CO 3 (CH 2 Cl 2 : H 2 O 10 : 1, 60 1C, 18 h), Ryu et al have been able to extend the scope and generality of the reaction including the possibility of coupling allylic bromides with alkenylboronic acids (56-95% yields). 32 The change of CH 2 Cl 2 for CHBr 3 together with an increase in the reaction temperature to 90 1C has permitted the reaction of electron-rich arylboronic acids with arylpropargylic bromides (13-84% yields). 33…”
Section: Transition-metal-free Suzuki Reactionsmentioning
confidence: 99%
“…In this reaction, a stoichiometric amount of n BuLi is used as a base to prepare (halovinyl)(propargyloxy)boron halides working as a key intermediate. In 2013, we reported the transition‐metal‐free cross‐coupling reaction of alkenylboronic acids and arylboronic acids with propargylic bromides in the presence of Cs 2 CO 3 as a base [Scheme (b)] , . Recently, Gandon and co‐workers found that the cross‐coupling reaction of propargylic alcohols with alkenylboronic acids proceeds efficiently by using Ca(NTf 2 ) 2 as a catalyst [Scheme (c)] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we 5 and the Scrivanti group 6 independently reported that a cross-coupling reaction between arylboronic acids and allylic bromides proceeded well without the use of a transition-metal catalyst to give the allylated products. Herein, we wish to report that a similar metal-catalyst-free reaction of arylpropargylic bromides with aryland alkenylboronic acids proceeded well to give propargylic products selectively (Scheme 1, eq.…”
mentioning
confidence: 99%